Perfluoro octanoic acid–modified magnetic hyperbranched polyamideamine as a sorbent for the extraction of fluorine‐containing pesticides from water samples. Issue 20 (3rd September 2021) - Meng, Zilin; Liu, Zikai; Fan, Jiaxuan; Li, Jing; Zhou, Wenfeng; Gao, Haixiang; Lu, Runhua
Abstract: Perfluoro octanoic acid was modified on the surface of magnetic hyperbranched polyamideamine by acid amine condensation. The morphology and chemical composition of perfluoro octanoic acid–modified magnetic hyperbranched polyamideamine was characterized by transmission electron microscopy, Fourier transform infrared spectroscopy, zeta potential, particle size analysis, Brunauer–Emmett–Teller measurement, and X‐ray photoelectron spectroscopy. Perfluoro octanoic acid–modified magnetic hyperbranched polyamideamine was applied in magnetic solid phase extraction for the separation and enrichment of four fluorine‐containing pesticides (indoxacarb, metaflumizone, cyflumetofen, and cyhalothrin). The magnetic solid phase extraction method based on perfluoro octanoic acid–modified magnetic hyperbranched polyamideamine has low method detection limits (0.30‒0.49 μg/L), a satisfactory coefficient of determination (0.9995‒0.9999), wide linear ranges (2.5‒250 μg/L), and good repeatability (intraday: 2.6‒4.7%; interday: 1.1‒7.9%). The enrichment factors and extraction efficiences varied from 55 to 76 and 69 to 96%, respectively. The sorbent‐to‐sorbent reproducibility was in the range of 3.2–7.6%, indicating that the synthesis of the sorbent was reliable. For the detection of actual water samples, the relative recoveries were in the range from 80.1 to 114.4% with relative standard deviations less than 9.6%. The calculation results of quantum chemistry calculations showed that after the modification of perfluoro octanoic acid, the interaction between the sorbent and four fluorine‐containing pesticides was stronger.